Behaving kindly, talking about it, and being rewarded for it?! - Gari Walkowitz; Oliver Gürtler; Daniel Wiesen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
In a principal-agent setup, we investigate agents disclosure of conflict of interests revealing deliberate or undeliberate kindness and its affect on principals reciprocal behavior. To this end, we firstly introduce a theoretical model refering to Hart and Moore (2008) which captures aspects of information revelation and reciprocal behavior. Secondly, a laboratory experiment (N = 444) tests behavioral predictions derived from the model. In the experiment, nature randomly determines the agent s choice set: either the agent can deliberately choose to behave kindly towards the principal (conflict of interest situation) or behaving kindly is the default. In any case, the agent can inform the principal about the available choice set. The principal can reciprocate the agent s behavior. We find agents to reveal their state when they are deliberately kind. Moreover, revealing a conflict of interest situation strongly triggers further reciprocal behavior by the principal. Our findings are robust towards different parameter variations. Implications are discussed.
Keywords: C91; D82; D01; 330